The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/ve/veac007
|View full text |Cite
|
Sign up to set email alerts
|

Intra-host analysis of hepaciviral glycoprotein evolution reveals signatures associated with viral persistence and clearance

Abstract: Even 30 years after the discovery of the hepatitis C virus (HCV) in humans there is still no vaccine available. Reasons for this include the high mutation rate of HCV, which allows the virus to escape immune recognition, and the absence of an immunocompetent animal model for vaccine development. Phylogenetically distinct hepaciviruses (genus Hepacivirus, family Flaviviridae) have been isolated from diverse species, each with a narrow host range: the equine hepacivirus (EqHV) is the closest known relative of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Model systems, such as the EqHV infections in equids, could help understand viral and host determinants required for species barrier crossing. For instance, recently, a study about intra-host diversity of EqHV and HCV shed light into viral determinants important for persistent hepacivirus infection and indicated the hypervariable region 1 in HCV as an important determinant in infecting the human population [ 33 ]. Furthermore, a previous study by Hoffmann et al 2020 found a divergent EqHV sequence in donkeys that differed by 22% from the reference strain which could have an impact on EqHV diagnostics in donkeys [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Model systems, such as the EqHV infections in equids, could help understand viral and host determinants required for species barrier crossing. For instance, recently, a study about intra-host diversity of EqHV and HCV shed light into viral determinants important for persistent hepacivirus infection and indicated the hypervariable region 1 in HCV as an important determinant in infecting the human population [ 33 ]. Furthermore, a previous study by Hoffmann et al 2020 found a divergent EqHV sequence in donkeys that differed by 22% from the reference strain which could have an impact on EqHV diagnostics in donkeys [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon transmission, fixation of mutations in RNA virus populations can occur through founder effect (limited genetic variability in the inoculum) or selective sweeps (an advantageous phenotype is swept to fixation) (For examples see ( Gömer et al, 2022 ) and ( Brown et al, 2012 )). As the dynamics of early innate immune activation differs between viral entry routes, we hypothesized that the resulting contrasting selective environments, in which early viral replication occurs, could influence the frequency or fixation of mutations in the cellular viral population.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for the apparent failure of the vaccine in Vaccine Pony 4 are not known. Investigation of the EqHV viral intrahost population composition of the genomic regions encoding E1 and E2 in experimentally infected horses revealed low bottleneck severity and high heterogeneity of the virus populations initiating infection [ 42 ]. Furthermore, intra-host viral diversification was observed over time [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the EqHV viral intrahost population composition of the genomic regions encoding E1 and E2 in experimentally infected horses revealed low bottleneck severity and high heterogeneity of the virus populations initiating infection [ 42 ]. Furthermore, intra-host viral diversification was observed over time [ 42 ]. Although intra-host heterogeneity of EqHV was shown to be less pronounced than for HCV [ 42 ], the potential roles in reducing vaccine effectiveness and inducing varied immune responses among hosts warrant consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation